Estrategias de regeneración urbano-arquitectónicas para barrios consolidados - Zambrano Castillo, Steven Christoper (2023)
The present proposal describes the elements, instruments, and tools necessary for the regeneration of consolidated neighborhoods, with special focus on Atocha in Ambato. This required conducting thorough research both on the territory and on theoretical, practical, and normative elements that enable the implementation of effective strategies in urban-architectural regeneration. The urbanarchitectural regeneration proposal for Atocha is based on delimiting the territory, identifying implementable strategies, and defining normative-legislative instruments for the success of the intervention. The aim is to revitalize consolidated areas with economic, social, and constructive activities, prioritizing pedestrianization, the development of endogenous socio-economic activities, and responsible densification. The importance of promoting architectural interfaces and heritage preservation is also emphasized. LOOTUGS is a key element in the proposal's implementation, aligning urban and architectural aspects with necessary regulations. The regeneration process must be comprehensive.